The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0168178
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Sequence Variation and Risk Association of Human Papillomavirus 52 Variants Circulating in Korea

Abstract: IntroductionHuman papillomavirus (HPV) 52 is a carcinogenic, high-risk genotype frequently detected in cervical cancer cases from East Asia, including Korea.Materials and MethodsSequences of HPV52 detected in 91 cervical samples collected from women attending Seoul St. Mary’s Hospital were analyzed. HPV52 genomic sequences were obtained by polymerase chain reaction (PCR)-based sequencing and analyzed using Seq-Scape software, and phylogenetic trees were constructed using MEGA6 software.ResultsOf the 91 cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…It has been recommended to use the complete genomes to identify HPV variant lineages and sublineages [6]. However, ambiguous assignment may arise when the The sublineage distributions of the four HPV types in China generated in this study were consistent with previous reports [16,[33][34][35][36][37][38][39][40]. However, with the intensification of globalization, the genetic diversity of HPV in China and other parts of the planet remains dynamic and requires continuous surveillance.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It has been recommended to use the complete genomes to identify HPV variant lineages and sublineages [6]. However, ambiguous assignment may arise when the The sublineage distributions of the four HPV types in China generated in this study were consistent with previous reports [16,[33][34][35][36][37][38][39][40]. However, with the intensification of globalization, the genetic diversity of HPV in China and other parts of the planet remains dynamic and requires continuous surveillance.…”
Section: Discussionsupporting
confidence: 76%
“…Rest of HPV52 sequences belonged to A1 (n=2), C2 (n=3) and D (n=1), and HPV58 to B2 (n=1). HPV52 lineages B and C were common in Asian countries, with B the most prevalent in China [34][35][36]. However, the cancer risk of HPV52 B variants was reported to be lower than lineage C [16].…”
Section: Genetic Diversity Of Verification Datasetmentioning
confidence: 99%
“…For HPV18, mutations related to carcinogenicity were rarely reported. For HPV52, Choi et al reported that A379G (E6 K93R) might be linked with higher disease severity and that this mutation was mainly occurred in sublineage B2 [31]. In our study, we showed that A379G mutation occurred in not only sublineage B2, but also in A2 and B1 (Supplementary Table S5).…”
Section: Discussionsupporting
confidence: 64%
“…These findings are in good agreement with a general trend in HPV52/58 variant distributions, suggesting that HPV52 lineage B and HPV58 lineage A are more prevalent in Asia than in Europe, the Americas, and Africa [ 16 , 32 ]. Further, a high prevalence of lineage B in HPV52-positive cervical specimens was reported in South Korea [ 33 ] and Taiwan [ 17 ], and the dominance of lineage A in HPV58-positive specimens was also observed in Taiwan [ 17 ], which strongly suggests that such biased distributions of HPV52/58 variant lineages are common among East Asian countries.…”
Section: Discussionmentioning
confidence: 98%